The chronicle of Dokdo 1905 - Yeh Young June (Seoul, Korea : Jun mi-jung, 2013)
"The most persuasive grounds on which Japanese claims its territorial rights on Dokdo rests on Japan's territorial incorporation on Dokdo in 1905. Korea views this territorial incorporation as the initiation of Japan's exploitation; that is, the prelude of the Eulsa Treaty in November 1905 and forceful annexation of Korea in 1910. When I found Yamaza Enjiro who contributed greatly to the exploitation of the Korean Peninsula by way of implementing numerous diplomatic tactics in collaboration with the Genyosha Ronin, I came to doubt if I could find a clue to solve the territorial issue in his story."--Publisher description.
Keywords: Tok Island (Korea) -- History -- 20th century